Improving writing skills of expository text with "˜think, talk, write' learning method - Budiyono, Sri; Sukini, Sukini; Warsihna, Jaka; Sutaji, Sutaji; Amertawingrum, Indiyah Prana (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2023)
This studi was aimed at describing the learning process of writing expository texts in class VII C SMP Ekakapti Karangmojo Gunungkidul, through the use of the TTW learning method. and describing the results of writing an exposition text for class VII C SMP Ekakapti Karangmojo Gunungkidul using the TTW learning method. This research is a Classroom Action Research (CAR). The technique of analyzing the data is using quantitative and qualitative techniques. Based on the results of the study, the conclusions that can be drawn are as follows. First, their exposition text writing skills have improved after using the TTW learning method. The improvement in writing exposition text skills was known from the pre-cycle, first cycle, and second cycle tests. The average score of their pre-cycle was 58.67. This result belongs to the poor category. Furthermore, for the average score in the first cycle the result was 75.63 so that it can be said to have increased and is included in the good category. Thus, there was an increase of 16.96% from the pre-cycle. In the second cycle, the average score achieved was 82.61. This result is included in the good category as well. Thus, there was an increase from the first cycle of 6.98% and 23.94% of the pre-cycle results. Second, learning to write Exposition texts through the TTW learning method has been proven to be able to change students' negative attitudes and behaviors into positive ones. These changes can make students who are less enthusiastic and less active become more alert, excited, happy, and able to enjoy learning. Students become more active in thinking (think), actively discussing (talk), and more actively writing exposition texts (write).